Properties of Soils and Classification in Megecha Subwatershed, Gurage Zone, Central Ethiopia: Implication for Soil Management - Alemu Wegu; Teshome Yitbarek; Isreal Zewide (Applied and Environmental Soil Science)
Description, characterization, and classification of soils are basics to have knowledge on soil properties that would be applicable for land use decisions and soil management strategies for optimum and sustainable agricultural production. The study was conducted at Megecha Subwatershed in Gurage Zone, Central Ethiopia. The purpose of the study was to study the soil properties of the watershed that would help to design appropriate soil management strategy for sustainable agricultural production. The study area was categorized into three slope positions (upper, middle, and lower) and four pedons were opened, and the soil description was made. A total of 17 disturbed and undisturbed soil samples were collected from each horizon. The results of the study revealed that the properties of the soils varied with the slope position and soil depth. Lower bulk density (ρb), darker red color, and soft (dry) consistency were observed at the upper slope position, whereas higher ρb, very dark gray color, and hard (dry) consistency were observed in the low slope areas. The pH values ranged from 5.3 to 6.3 (moderately to slightly acidic), soil organic carbon from 0.58% to 2.99% (low to high), and available phosphorus (P) from 0.28 to 1.20 mg·kg−1, rated as low and total nitrogen (N) and 0.02% to 0.27% (very low to high). Regarding the soil classification, Pedon 1 is classified as Chromic Alisols (Epidystric); Pedon 2, Chromic Alisols (Dystric); Pedon 3, Haplic Alisols (Dystric); and Pedon 4, Pellic Vertisols (Hypereutric). The soil map was developed for these identified soil types. The spatial variability of the soils should be taken into consideration for the sustainable soil management strategy.